Bridging the Urban-rural divide? A case study on rural land transition in Sichuan Province, China - Yan Song; Qinlin Gong; Christine Boyle (Journal of Urban Management, 2013)
Rising concern over urban-rural economic disparity in China in the early 2000s spurred a series of policy initiatives to improve people's quality of life in rural areas. A recently launched Rural Land Transition Program in Sichuan Province aims to increase land-use efficiency and rural incomes by consolidating fragmented land plots under large commercial firms for agricultural production. In this paper, we document the scheme of implementation of the land transition project through the pilot case of Renshou Village in Sichuan Province, drawing attention to its contested premise. The paper suggests that the goals of achieving greater economies of scale in agricultural production and increasing rural incomes via land consolidation have met with mixed success.
Keywords: 710; China; land consolidation; rural land reform; Rural land transition; urban-rural disparity